2019
DOI: 10.1186/s13148-019-0671-8
|View full text |Cite
|
Sign up to set email alerts
|

Functional roles of lncRNAs and its potential mechanisms in neuropathic pain

Abstract: Neuropathic pain (NP) is ranked as one of the major forms of chronic pain and emerges as a direct consequence of a lesion or disease affecting the somatosensory nervous system. Despite great advances into the mechanisms of NP, clinical practice is still not satisfactory. Fortunately, progress in elucidating unique features and multiple molecular mechanisms of long non-coding RNAs (lncRNAs) in NP has emerged in the past 10 years, suggesting that novel therapeutic strategies for pain treatment may be proposed. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 90 publications
0
12
0
Order By: Relevance
“… 6 , 7 Accumulating evidence indicates that lncRNAs are involved in various processes of cellular activities, such as adipogenesis, apoptosis, pyroptosis, cell differentiation, epigenetic modification, and tumorigenesis and modulation. 8–13 They regulate genomic expression and posttranscription in cis or trans by interacting with chromatin, protein, and RNA in the nucleus or cytoplasm. Li et al 14 reported that lncRNA-MALAT1 can suppress inflammatory responses by increasing miR-146a expression in lipopolysaccharide (LPS) -treated ALI.…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 7 Accumulating evidence indicates that lncRNAs are involved in various processes of cellular activities, such as adipogenesis, apoptosis, pyroptosis, cell differentiation, epigenetic modification, and tumorigenesis and modulation. 8–13 They regulate genomic expression and posttranscription in cis or trans by interacting with chromatin, protein, and RNA in the nucleus or cytoplasm. Li et al 14 reported that lncRNA-MALAT1 can suppress inflammatory responses by increasing miR-146a expression in lipopolysaccharide (LPS) -treated ALI.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, lncRNAs have become a research hotspot in the diagnosis and prevention of disorders of the nervous system [28,29]. Numerous studies have confirmed that lncRNAs play a crucial role in the etiopathogenesis of NP [30][31][32]. CRNDE has been extensively investigated in several malignant tumors and has been identified as a tumor promoting factor [33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Refractory diseases such as NP are a worldwide health problem. Functional roles of lncRNAs and their potential mechanisms in NP have been reviewed in the previous literatures [70, 71]. The levels of lncRNAs have been reported to be significantly altered in the spinal cord of an animal model of spared nerve injury [72, 73].…”
Section: Lncrnas In Scimentioning
confidence: 99%